Medical slang in Rio de Janeiro, Brazil - Peterson Christopher (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
The author analyzes medical slang in Rio de Janeiro based on the view of interactive or live metaphor proposed by such authors as Black and Ricoeur, applied to puns and other jokes from medical work, with the goal of unveiling what physicians mean by this linguistic register. The article classifies medical slang in three broad areas, pertaining to the physician's relations with professional training and knowledge, patients, and health care services. Comparing his empirical material with previous studies focusing on hospital slang for patients, the author identifies, in addition, a range of slang terms for health care services themselves. The article points to interfaces between medical slang and the Brazilian "health hypercrisis" identified by Schramm.